STUDI PERFORMASI SUDU TURBIN ANGIN SAVONIUS TIPE VERTICAL AXIS BERBAHAN KOMPOSIT - Ozkar F. Homzah; Ella Sundari; Rachmat Dwi Sampurno; Ogi Meita Utami; Lily Rahmawati (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
The increasing human population, the use of fossil energy such as oil also increases. While fossil energy is one of the largest contributors to carbon emissions that can cause climate change that can be done to control climate change is to switch to the use of renewable energy. The investigation takes the shape of a vertical axis Savonius turbine blade design. The blades are made of a composite material called carbon fiber, and the number of blades varies between 4, 6, and 8 pieces. The study's findings were tested utilizing a blower-generated wind source with wind speeds of 4m/s, 4.5m/s, and 5m/s. A wind tunnel consisting of acrylic material and pipes as a frame construction was used in the test. The test findings show that turbine blades with a total of four blades produce the maximum generator power of 0.274 watts at a wind speed of 5 m/s. Meanwhile, the turbine blade with 8 blades has the lowest output power at a wind speed of 4 m/s and a power value of 0.0028 W. Then, with 8 blades, it has a relatively low output energy compared to 4 and 6 blades. Therefore, the highest efficiency performance of wind turbine use is achieved by a turbine with a number of 4 blades with a maximum efficiency is 9,16% and the minimum efficiency it seen in a wind turbine with a number of blades 8 within 0,07%.